Numerical simulation of the casting process - Bowles_HC (Department of Mechanical Engineering, 2023)
The increasingly competitive market for cast products has required the development of higher quality and lower cost products. Although conventional process development techniques have improved, the cost and time associated to process development needs to be reduced. A faster and more cost-effective development method is required. Numerical modelling techniques provide a means by which casting design and process parameters can be optimized with minimum use of prototypes. This thesis reviews the current state of the art in solidification modelling. A typical casting problem is modelled, and the numerical results compared against measured temperatures. further work is required to from this investigation it is concluded that obtain, and accurately model the material properties and complex radiation behaviour within the fibrous insulation.